Canadian Pamphlets and Broadsides - Thomas Fisher Rare Book Library
This collection provides access to the pre-1930 Canadian pamphlet and broadside holdings of the Thomas Fisher Rare Book Library by supplying both page images in full colour, and full searchability of the contents of each item. To date the site consists of 597 broadsides (single sheets, printed on one or both sides) and 2,062 pamphlet titles which amounts to 71,508 page images. The collection includes items printed in Canada, by Canadian authors, or about Canadian subjects, mainly of a non-literary nature.
Keywords: _open access

French Revolution Digital Archive
Keywords: _open access